Implementasi Ḥudūd di Indonesia Menurut Abdullāh bin Bayyah - Wafa, Muhammad Shidqi; Hanani, Muhamad Saiq (Syariah: Journal of Fiqh Studies, 2024)
The debate regarding ḥudūd creates differences in opinions among muslims. Some believe it is necessary to apply ḥudūd as an inseparable part of Shari'a without considering the context. Others argue that this concept needs to be reinterpreted according to current times. There are also moderate views that try to harmonize the two perspectives, including the view of Abdullāh bin Bayyah, who emphasizes harmonization between text and context to achieve a balanced understanding. Therefore, this research aims to analyze Abdullāh bin Bayyah's views on ḥudūd and the relevance of his views to criminal law in Indonesia. To achieve these objectives, the method used in the research is content analysis, which is classified as a qualitative method whose analysis is descriptive. Abdullāh bin Bayyah saw ḥudūd as part of Allah's noble law to prevent evil. ḥudūd punishment is considered superior in handling serious crimes. However, its implementation involves a serious evaluation of legal aspects such as causes, conditions, and māni' (hindrances). Before applying ḥudūd, it is necessary to tahqīq al-manāṭ to understand its consequences. Abdullāh bin Bayyah's view has relevance to criminal law in Indonesia, his view gives legitimacy to the Criminal Code as long as the risk of mafsadah enforcing ḥudūd is greater than not enforcing it. Even though ḥudūd has not been implemented in Indonesia, this view does not eliminate the possibility that the government and legislators continue to be responsible for understanding and analyzing reality according to current developments.